Oxidative Stress and Down Syndrome: A Systematic Review - Goran Slivšek; Sandra Mijač; Ivan Dolanc; Marija Fabijanec; Silvija Petković; Renato Mautner; Karmen Lončarek; Josip Kranjčić; Alenka Boban Blagaić; Marin Marinović; Ksenija Vitale; Donatella Verbanac; et al. (Antioxidants)
Down syndrome (DS), the most common human aneuploidy, is associated with oxidative stress, which contributes to morphological abnormalities, immune dysfunction, cognitive impairment and accelerated ageing. This article aims to provide an overview of the studies on oxidative stress in DS, in particular the investigation of endogenous and exogenous antioxidants, with a focus on endogenous systems. A literature search in MEDLINE and Scopus based on the PRISMA 2020 criteria revealed 41 relevant studies that mainly analysed blood samples (plasma or serum) and occasionally saliva or urine. The findings suggest that oxidative stress in DS is multifactorial and results from an imbalance of superoxide dismutase activity, overexpression of genes on chromosome 21, mitochondrial dysfunction and inflammation. Despite extensive studies over the decades, new sources and mechanisms for oxidative stress in DS continue to emerge, further highlighting the complexity of DS. The recognition that oxidative stress is a hallmark of DS emphasises the need to develop more sensitive and specific methods to detect it and to investigate the associated metabolic pathways in DS in more detail. The expansion of in vivo studies could facilitate the development of targeted interventions aimed at mitigating oxidative damage and ultimately improving outcomes for individuals with DS.